Genetics in early cancer diagnosis - Jakubowska, A.; Górski, B.; Cybulski, C.; Kurzawski, G.; Gronwald, J.; Huzarska, J.; Kładny, J.; Lubiński, J.; Menkiszak, J.; Krzystolik, K.; Hadaczek, P.; Zajączek, S.; et al. (Contemporary Oncology/Współczesna Onkologia, 2000)
On the basis of our own experience and literature data authors summarized value of genetcs in detection of herediance.